Base‐Catalyzed Domino Michael–Alkylation–Rearrangement Reaction: A Synthetic Route to Functionalized 2, 3‐Dihydrofurans. Issue 15 (10th April 2014) - Zhang, Ren‐Zun; Meng, Chang‐Yu; Xie, Jian‐Wu; Xu, Mei‐Lan; Zhu, Wei‐Dong
Abstract: An unexpected and efficient domino reaction of N ‐sulfonyl‐1‐aza‐1, 3‐dienes with 2‐halo‐1, 3‐dicarbonyl compounds to synthesize differently substituted 2, 3‐dihydrofuran derivatives with excellent regio‐, chemo‐, and stereoselectivity in moderate to good yields was developed. In this transformation, broad substrate scope was demonstrated, and a plausible mechanism for this novel domino reaction was given. Abstract : A method for the synthesis of substituted 2, 3‐dihydrofuran derivatives through a domino Michael–alkylation–rearrangement reaction is developed. In this transformation, broad substrate scope is demonstrated, and a plausible mechanism for this novel domino reaction is given. Ts = para ‐tolylsulfonyl, Lg = leaving group.